Enhancing Students' Understanding of the Islamic Golden Age during the Abbasid Caliphate through Problem-Based Learning - Haizatul Masnaiyah; Iwan Marwan (Allimna: Jurnal Pendidikan Profesi Guru, 2025)
This classroom action research describes how problem-based learning improves students' understanding of the Golden History of Islam during the Abbasid Daulah (750 to 1258 AD) at NU Sabilil Huda Junior High School. The study involved 19 grade VIII A students at NU Sabilil Huda Junior High School, Kediri. The research adopted the Kemmis and Taggart model, using observation, interviews, and questionnaires, and the data were analyzed descriptively. The research was conducted in two cycles, each comprising planning, action, observation, and reflection. The results show that problem-based learning significantly improved students' understanding of the Golden History of Islam during the Abbasid period. This improvement is evidenced by an increase in the average test score from 75.6 in Cycle 1 to 82.1 in Cycle 2, as well as an increase in student mastery from 47.4% to 84%. Students also demonstrated an improved ability to analyze the relationships among art, science, and civilization. Thus, it can be concluded that problem-based learning is effective in improving students' understanding of Islamic Golden Age history and can be recommended for similar historical materials in Islamic Religious Education to enhance students' critical thinking and conceptual understanding.